Addition of Probiotic EM4 in Feed Against The Growth and Survival Rate (Oreochromis niloticus) in Controlled Condition - Nasmia, Nasmia; Wardoyo, Rahmat Wahyu Bumi (AgriSains, 2021)
This study aims to determine the effect of adding probiotics in feed on growt and survival rate of tilapia. This study was designed using a Completely Randomized Design (CRD), with a P factor (Probiotic EM4) consisting of 4 treatments with 5 replications each so that there were 20 experimental units. The addition of EM4 probiotics in tilapia feed gave significant effect (P>0,05) on absolute weight growth, specific growth rate. The survival rate of tilapia with the treatment of adding EM4 probiotics in feed ranges between 82-86%.